2011
DOI: 10.1080/13623699.2011.607733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medical supplies essential for the care of survivors of sex- and gender-based violence in post-conflict Eastern Democratic Republic of Congo

Abstract: The fundamental concepts set forth in the formal Post-Conflict Needs Assessment (PCNA) initiative created by the United Nations Development Group have the potential to be adapted to assist local groups in documenting the needs of and the provision of health care to survivors of sex- and gender-based violence (SGBV) in Eastern Democratic Republic of Congo (DRC). In partnership with Congolese health care providers, we took the first step in advocating for a locally-adapted and focused needs assessment through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our systematic review yielded 2087 documents, among which only 27 were original studies either based on population surveys (20) or presenting original data based on case studies and reviews (7). Ten studies provided prevalence rates of rape victims; 18 provided specific information on the profile of the victims; 10 reported that most of the perpetrators of rape were military personnel; 14 referred to the negligence of the government in protecting victims; and 10 reported a lack of competent health care facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our systematic review yielded 2087 documents, among which only 27 were original studies either based on population surveys (20) or presenting original data based on case studies and reviews (7). Ten studies provided prevalence rates of rape victims; 18 provided specific information on the profile of the victims; 10 reported that most of the perpetrators of rape were military personnel; 14 referred to the negligence of the government in protecting victims; and 10 reported a lack of competent health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Some recall bias may also exist when information was given by the victims themselves because of faulty memories. Furthermore, there may be certain communication difficulties between researchers and victims not only due to language problems but also due to cultural aspects: Indeed, the majority of investigators were foreigners (Europeans or Americans), making it potentially difficult for victims to Studies 3,24,and 26 Profile of the rape perpetrators Studies: 1, 2, 4, 5, 7, 11, 13, 15, 16, and 25 Profile of the victims Studies: 2, 3, 4, 5, 6, 7, 11, 12, 13, 14, 16, 17, 18, 19, 21, 22, 23, and 25 Health structures, access to health services Studies: 4, 5, 9, 12, 13, 15, 20, 21, 25, and 26 Role of States Studies: 7, 8, 10, 11, 12, 15, 16, 17, 19, 20, 21, 22, 26, and 27 Consultation of an ethics committee Yes No Studies: 1,4,6,7,8,18,20,24,and 27 Studies: 2,3,5,9,10,11,12,13,14,…”
Section: Strengths and Weaknesses Of The Studiesmentioning
confidence: 99%
“…Moreover, for the minority, who are able to overcome the above‐mentioned sociocultural barriers and access services, there is inadequate health infrastructure and personnel (Rybarczyk et al., ). The health system of the DRC, once considered one of the best in Africa, suffered near total collapse between 1995 and 2001 because of the ongoing conflict (Waldman, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 70% of the DRC population have little or no access to health care (Waldman, ). Moreover, the health system currently has no resources to provide the much‐needed psychological assistance and support to the survivors of SV (Rybarczyk et al., ).…”
Section: Introductionmentioning
confidence: 99%